Mechanism of Laccase Induction via Emodin in Trametes versicolor - Wang, Lin; Luo, Xuecai; Pan, Yu; Zheng, Zai; Yin, Ruochun; Tian, Xiaohe; Zhang, Liang (Frontiers in Bioengineering and Biotechnology, 2021)
Secondary metabolites of traditional Chinese herbs can prominently stimulate the production of laccase from white rot fungi during submerged fermentation. However, the molecular mechanism through which these natural products induce the production of laccase remains unknown due to limited microscopy resolution. In this study, using the aid of a super-resolution method, the Chinese herbal medicine Polygonum cuspidatum was used to induce laccase production in Trametes versicolor, and the best inducer was identified in emodin, even under conditions of 1000-L, large-scale fermentation. Proteomics analysis identified a selection of proteins that were differentially expressed in the presence of emodin, indicating that emodin may affect the expression of laccase genes through three mechanisms: reducing bioenergy productivity, the aryl hydrocarbon receptor (AHR)/xenobiotic response element (XRE) pathway, and the nuclear erythroid 2-related factor 2 (Nrf2)/antioxidant response element (ARE) pathway. Stimulated emission depletion (STED) nanoscopy revealed that emodin might reduce the synthesis of ATP by lowering the mitochondrial membrane potential, leading to the subsequent responses.